2022
DOI: 10.1177/1759720x221080375
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in juvenile idiopathic arthritis: maternal and foetal outcome, and impact on disease activity

Abstract: Objective: This retrospective cohort study describes the modulation of disease activity during gestation and in the year following delivery as well as maternal and neonatal outcomes in a monocentric cohort of women with juvenile idiopathic arthritis (JIA). Methods: Disease activity was assessed using DAS28-CRP before conception and every 3 months during pregnancy and in the first year postpartum. The risk of complicated pregnancies was measured applying a generalized estimating equation model. Changes in disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This is supported by prior studies which reported an association between adverse pregnancy outcomes and high clinical disease activity in patients with inflammatory arthritis. 7,15,33,34 Our study also had several findings that have been similarly reported in other studies on this population: patients with RA/JIA in our study have higher rates of C-sections and pre-eclampsia; 6,26,28,35 however the rates of stillborn are the same as individuals without RA/JIA. 6 From our mediation analysis, we found that PEC accounted for only about 4% of fetal growth restriction.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is supported by prior studies which reported an association between adverse pregnancy outcomes and high clinical disease activity in patients with inflammatory arthritis. 7,15,33,34 Our study also had several findings that have been similarly reported in other studies on this population: patients with RA/JIA in our study have higher rates of C-sections and pre-eclampsia; 6,26,28,35 however the rates of stillborn are the same as individuals without RA/JIA. 6 From our mediation analysis, we found that PEC accounted for only about 4% of fetal growth restriction.…”
Section: Resultssupporting
confidence: 90%
“…This is supported by prior studies which reported an association between adverse pregnancy outcomes and high clinical disease activity in patients with inflammatory arthritis. 7,15,33,34…”
Section: Resultsmentioning
confidence: 99%
“…Women with JIA had stable low disease activity or inactive disease in pregnancy. This has also been demonstrated in other cohorts of pregnant women with JIA the last decades (12,13,(25)(26)(27). A possible association with active JIA in pregnancy has been investigated in two earlier studies, with conflicting results (13,17).…”
Section: Discussionmentioning
confidence: 87%
“…The research interest about reproductive issues in women with JIA has flourished only over the recent years, explaining why available data regarding obstetric and neonatal outcomes in JIA are still scanty and not consistent. Discrepancies concern the fluctuation of JIA disease activity during pregnancy: earlier studies suggested improvement of disease activity during gestation [21,33,80], while more recent investigations have reported a high rate of flares during gestation [81][82][83][84][85]. In particular, the latter have shown that disease activity remains substantially stable in the first trimester to significantly increase in the second trimester.…”
Section: Pregnancy In Juvenile Idiopathic Arthritismentioning
confidence: 98%
“…Indeed, most data come from population-based studies analysing administrative health databases or hospital discharge records, which do not allow for adequate accounting for potential confounders, including JIA category. According to available reports, disease activity tends to peak again in the post-partum [33,80,[83][84][85]; it is important to note that the sooner bDMARDs are reintroduced after delivery, the sooner disease control is obtained [84]. There is a substantial consensus in literature reporting preterm delivery and low neonatal birth weight as the main obstetric complications among JIA women [84,[86][87][88][89][90][91], while data about the risk of PE in JIA pregnancies are conflicting [80,84,90,92,93].…”
Section: Pregnancy In Juvenile Idiopathic Arthritismentioning
confidence: 99%